Integrable modules for loop affine-Virasoro algebras. Issue 12 (2nd December 2021) - Rao, S. Eswara; Sharma, Sachin S.; Mukherjee, Sudipta
Abstract: In this article, we classify the irreducible integrable modules for the loop affine-Virasoro algebra ( ( g ° ⊗ C [ t, t − 1 ] ⊕ C K ) ⋊  Vir ) ⊗ A, where A is a finitely generated commutative associative unital algebra over C .